Analisis mutu air Danau Area Gelanggang Expo dengan metode indeks pencemaran di kota Jayapura - Prasetia, Angga; Walukow, Auldry F (Dinamika Lingkungan Indonesia, 2021)
This study aims to determine the current status of lake water quality in the Gelanggang Expo area using the Pollution Index (IP) method. It is found that there has been pollution in Lake Sentani with high concentrations of certain pollutants, such as Nitrite as NO2-N (0.06 - 0.15 mg/L), Phosphate as PO4-P (0.2 - 0.45 mg/L), Sulfide as S-H2S (0.002 - 4.26 mg/L), Cadmium (0.01 - 0.3 mg/L), Chromium valence 6 (0.05 - 0.26 mg/L), Copper (0.02 - 2.15 mg/L), Zinc (0.05 - 0.5 mg/L), Phenolic compounds (1 - 9.53 μg/L), and free chlorine (0.03 - 2, 1 mg/L). The concentration of these substances has exceeded the quality standard set by the government through PP 82 of 2001 concerning water quality management and water pollution control. The status of the lake water quality in the Gelanggang Expo area is declared moderately polluted with an IP value of 6.78. Sentani lake pollution is caused by eight parameters that have exceeded the quality standard, namely temperature, BOD, COD, Sulfide, Pb, Cu, Phenol, and free chlorine.